Effect of Wildebeest Migration Pattern on Sustainability of Tourism Development at Mara-Serengeti Ecosystem: A Transboundary Resource Management Perspective (Global Journal of Management and Business Research, 2022)
Sustainable tourism development in the Serengeti-Mara region seemingly depends largely on the wildebeest migration phenomenon This is particularly due to its appeal to the tourist and its classification as one of the new wonders of the world by UNESCO The phenomenon has over the years been used as a flagship marketing tool to project the ecosystem as a leading tourism destination